KAJIAN SUBSIDI DAN PENJAMINAN PEMERINTAH DALAM PROYEK PENYEDIAAN AIR MINUM BERDASARKAN PRINSIP SYARIAH - MUHAMMAD ZAINUL ABIDIN (Al Qalam, 2013)
This study aims to determine the possibility of granting of guarantees and interest subsidies by central government in· order to accelerate the provision of drinking water, as stated in the Presidential Regulation 29 of 2009, based on Islamic principles. This research uses descriptive qualitative method. Collecting the data used in this study using the literature study. Data collected through the research literature related to the topic of study to obtain secondary data. It was concluded that the government guarantee as stipulated in the Presidential Regulation 29 of 2009 can be implemented based on Islamic financing and using the kafalah and the qardh contracts. The Kafalah contract put. the Government as guarantor (kafil).The Qardh contract implementation would be used in the event of payment of guarantee claims. The Qardh put the Government as provider of funds for payment to Islamic banking. Upon payment of warranty claims, the Government may request repayment to PDAM and local government. The interest subsidy in the Presidential Regulation 29 of 2009 can be converted into margin subsidy using the Hawalah contract, the Government accept the transfer of liability to the bank On the basis of the realization of partial payment obligations through subsidy mechanism, the Governement waived the right to claim to PDAM. Keywords: Government Guarantee, Interest Subsidy, Islamic Financing; The Fast Track Program Of Water Supply